The answer to your question is 3
Ugh, these questions.
21x^3y^4 + 15x^2y^2 - 12xy^3
3xy^2 (7x^2y^2 + 5x - 4y)
Clearing up clutter...
3xy² (7x²y² + 5x - 4y)
That's your answer. Thanks for working my brain. ;)
Answer:
x = 10°
Step-by-step explanation:
a). Since, opposite angles of a cyclic quadrilateral are supplementary angles"
Therefore, in cyclic quadrilateral ABDE,
m∠ABD + m∠AED = 180°
110° + m∠AED = 180°
m∠AED = 180° - 110°
= 70°
b). AD = ED [Given]
m∠EAD = m∠AED [Since, opposite angles of equal sides are equal in measure]
m∠EAD = m∠AED = 70°
By triangle sum theorem in ΔABD,
m∠BAD + m∠ABD + m∠ADB = 180°
m∠BAD + 110° + 40° = 180°
m∠BAD = 180 - 150
= 30°
m∠AEB = m∠AED + m∠DAB [By angles addition postulate]
m∠AEB = 70° + 30°
= 100°
By triangle sum theorem in the large triangle,
x° + m∠AEB + m∠EAB = 180°
x° + 100° + 70° = 180°
x = 180 - 170
x = 10°
Answer:
(- 2, 6 )
Step-by-step explanation:
Given the equations
3x + 2y = 6 → (1)
y - x = 6 ( multiply through by 3 to clear the fraction )
2y - 3x = 18 ( add 3x to both sides )
2y = 18 + 3x → (2)
Substitute 2y = 18 + 3x into (1)
3x + 18 + 3x = 6
6x + 18 = 6 ( subtract 18 from both sides )
6x = - 12 ( divide both sides by 6 )
x = - 2
Substitute x = - 2 into (1) and solve for y
3(- 2) + 2y = 6
- 6 + 2y = 6 ( add 6 to both sides )
2y = 12 ( divide both sides by 2 )
y = 6
solution is (- 2, 6 )